Luciferase reporter assay for small-molecule inhibitors of MIR92b-3p function: Screening cyanopeptolins produced by Nostoc from the Baltic Sea. (October 2020) - Brzuzan, Paweł; Mazur-Marzec, Hanna; Florczyk, Maciej; Stefaniak, Filip; Fidor, Anna; Konkel, Robert; Woźny, Maciej
Abstract: We developed a cell sensor that detects the liver cancer-specific microRNA MIR92b-3p, involved in hepatocellular carcinoma development and hepatitis C virus infection. To validate our small-molecule screen that employs a Huh7 human hepatoma cell line stably transfected with a pmirGLO vector containing dual luciferase reporters, we used i) a MIR92b-3p antisense or a MIR92b-3p mimicking agent (concentrations from 0.1 pM to 100 nM), ii) expression of XIST, a long non-coding RNA that is a cellular target of MIR92b, and iii) ectopic expression of Luc2 luciferase. This reporter system was used to test four cyanopeptolins from a de novo library of peptides that were isolated from the Baltic Sea cyanobacteria Nostoc edaphicum strain CCNP1411. Exposure of the Huh7-pmirGLO-MIR92b-3p cells to increasing concentrations (from 10 nM to 100 μM) of the cyanopeptolins and microcystin-LR (MC-LR; a treatment control) did not lead to a dose-dependent restoration of the luciferase signal. Instead, when the reporter cells were treated with MC-LR, the luciferase signal decreased markedly, most likely due to non-target, toxic effects of MC-LR on the cells. Although the first use of this reporter system to screen selected Nostoc peptides did not identify inhibitors of MIR92b, this method provides a means to identify functional miRNA regulators and could be readily extended to other compounds. Graphical abstract: Unlabelled Image Highlights: The Cyanobacterium, Nostoc edaphicum CCNP 1411, is a rich source of bioactive compounds. MIR92b contributes to the pathogenesis of human diseases, including cancer. A small-molecule screen to detect MIR92b-3p regulators was developed in the Huh7 cell line. The approach with four Nostoc cyanopeptolins did not identify inhibitors of MIR92b. The high-throughput compatible procedure provides a means to identify functional miRNA regulators.